2014
DOI: 10.1007/s10493-014-9857-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of the integument with respect to different modes of locomotion in the Nematalycidae (Endeostigmata)

Abstract: Previous research on the locomotion of the Nematalycidae has only been undertaken on Gordialycus, which is by far the most elongated genus of the family. Gordialycus is dependent on an unusual form of peristalsis to move around. It was not known whether the genera of Nematalycidae with shorter bodies also used this mode of locomotion. Our videographic recordings of Osperalycus did not reveal peristalsis. Instead, this mite appears to move around the mineral regolith via the expansion and constriction of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The problem here is the absence of unequivocal morphological apomorphies supporting either the clade including most Endeostigmata or Euacariformes. We found a single character in support to the Endeostigmata clade: Nematalycidae presents cuticle projections known as palettes, which are oriented so that their edges are perpendicular with respect to the surface annuli, aiding in the grip of the body against the interstitial surface [ 61 ]. These palettes have also been found in the Nanorchestidae [ 62 ] where their function is uncertain, and some superficially similar structures may be seen in Bimichaelia (Alycidae) (SEM pictures in [ 63 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The problem here is the absence of unequivocal morphological apomorphies supporting either the clade including most Endeostigmata or Euacariformes. We found a single character in support to the Endeostigmata clade: Nematalycidae presents cuticle projections known as palettes, which are oriented so that their edges are perpendicular with respect to the surface annuli, aiding in the grip of the body against the interstitial surface [ 61 ]. These palettes have also been found in the Nanorchestidae [ 62 ] where their function is uncertain, and some superficially similar structures may be seen in Bimichaelia (Alycidae) (SEM pictures in [ 63 ]).…”
Section: Discussionmentioning
confidence: 99%
“…However, live specimens of Osperalycus tenerphagus Bolton & Klompen were collected and mounted for LT-SEM by directly removing them from floated material that had not yet been sieved. This was accomplished by placing the floated material directly under a dissection microscope (see also Bolton et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Like other nematalycids, Osperalycus and Gordialycus appear to live exclusively in mineral soils or sands. Their unusual integumental morphology is clearly well adapted for moving around in these habitats (Bolton et al, 2015). Gordialycus is frequently found in deserts, beaches and sand dunes (see appendix; Coineau et al, 1967;Silva et al, 1989;Norton et al, 2008).…”
Section: Ecological Relevance Of the Rupturing Mechanismmentioning
confidence: 99%
“…But if Nematalycidae are paraphyletic, they would have to be older than the Eriophyoidea, which originated no later than the Triassic (c. 230 Ma) (Schmidt et al 2012;Sidorchuk et al 2015). Accordingly, the highly elongated body and unusual modes of locomotion (Bolton et al 2015b) of Nematalycidae would represent a relatively early departure from the primitive body form and mode of locomotion of Acariformes.…”
Section: The Eriophyoidea + Nematalycidae Cladementioning
confidence: 99%
“…By comparison, in Trombidiformes the movable digits of the chelicerae appear to have sunken into a preoral groove in the subcapitulum (de Lillo et al 2001;di Palma et al 2009); membranous extensions have not been observed. Eriophyoidea and Nematalycidae also share another unusual feature: they have anal valves (modified into lobes in Eriophyoidea) that are used to anchor the idiosoma in place (Baker et al 1987;Lindquist 1996b;Bolton et al 2015b).…”
Section: Introductionmentioning
confidence: 99%